Puck control in relation to the success of the team in the game of a penalty kill of an ice hockey player - Blanar, M. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
In this research we have focused on the detection of differences in puck control in penalty kills in relation to their success in ice hockey matches in the Slovak Extraliga seniors League. We have been watching matches of the Slovak hockey league and using an indirect research, in which we analyzed the 75 games in penalty kills within 5 teams in terms of puck control. To find significance of the differences in the puck control of the successful and unsuccessful penalty kills we used the Mann-Whitney U-test. We evaluated the differences at 5% and 1% level of statistical significance. We found that the success of the team in the game in a penalty kill was significantly linked to the length of the puck control and check that the puck control of the team in the game in the penalty kill is relatively evenly distributed in all three zones. The work brought results, which can be useful in making training process, increase the performance of team game in the match, and to some extent, to enrich the theory of the game of ice hockey.